Relasi Kuasa dan Eksploitasi Terselubung dalam Lingkungan Kerja Tenaga Medis: Perspektif Etis dan Hukum terhadap Praktik Tidak Patut - Esa Meirianna; Ahmad Ma’mun Fikri (CV Rewang Rencang, 2025)
This research discusses the practice of covert sexual exploitation or white collar pimping perpetrated by certain individuals in Human Resource Development (HRD) against female doctors in remote areas. Using methods such as grooming, pseudo-mentoring, conditioning private meetings, and non-clinical requests, female doctors are manipulated into situations of unequal power. This study employs a qualitative-descriptive approach and normative legal analysis. It was found that HRD's involvement in facilitating unethical relationships between doctors and organizational leaders constitutes a violation of civil law and professional ethics. This article also examines the legal consequences for organizational leaders and other employees involved. These findings underscore the urgency of establishing an independent reporting system and organizational policies that protect female medical personnel in remote areas.